A high-sensitivity air pressure sensor with short desorbing time. (February 2023) - Li, Hao; Xu, Mingjing; Song, Hongbin; Zhou, Ai
Graphical abstract: Highlights: The MZI sensor is composed of silica fiber and MOF-PDMS material. Due to the excellent gas adsorption characteristics of PDMS, the air pressure sensitivity of the sensor can reach 86.79 nm/Mpa, which is nearly 10 times that of the traditional pure fiber air pressure sensor. The introduction of the MOF greatly accelerates the air desorption in the PDMS. Experimental results show that the recovery time of the sensor at 100 kPa was 20 s, which was significantly reduced compared with the 6-minute recovery time of the sensor with only PDMS sensing materials. The fabrication method of the MOF-PDMS mixture in the sensing structure was simple and convenient. Abstract: We proposed and confirmed a highly sensitive gas pressure sensor based on a fiber Mach-Zehnder interferometer, which uses polydimethylsiloxane (PDMS) and metal–organic frameworks (MOF) mixture as gas-sensitive material. PDMS is naturally sensitive to air pressure because its refractive index changes dramatically with the variation of gas pressure. However, due to its small pore size, the gas desorption time is usually long. By introducing MOF with large-size pores and large porosity into PDMS, the multiple channels connected with the outside in PDMS can be established, so that the gas in PMDS can be rapidly desorbed through the channels. Experimental results show that the air pressure sensitivity is 86.7 nm/MPa in the range of 0.08–0.28 Mpa, and the desorption time is shortened to 1/18 of that of pure PDMS.